The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1161/atvbaha.116.307291
|View full text |Cite
|
Sign up to set email alerts
|

Serum Angiopoietin–Like Protein 2 Is a Novel Risk Factor for Cardiovascular Disease in the Community

Abstract: Objective-Angiopoietin-like protein 2 (ANGPTL2), a proinflammatory mediator, has been reported to accelerate the development of insulin resistance, endothelial dysfunction, and atherosclerosis in mice. However, no cohort studies have examined the relationship between serum ANGPTL2 levels and the development of cardiovascular disease (CVD) in a general population. Approach and Results-A total of 3005 community-dwelling Japanese aged ≥40 years without a history of CVD were divided into 4 groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 24 publications
0
37
1
Order By: Relevance
“…9e ). On the other hand, to date we and others have independently reported that circulating ANGPTL2 levels increase in various pathological conditions other than obesity accompanied by adipose tissue inflammation, such as atherosclerotic vascular disease and type 2 diabetes and that these levels are associated with disease severity 17 20 39 40 41 . Because, some of these conditions are risk factors for HF development, further studies are needed to investigate whether circulating ANGPTL2 affects cardiac function.…”
Section: Discussionmentioning
confidence: 89%
“…9e ). On the other hand, to date we and others have independently reported that circulating ANGPTL2 levels increase in various pathological conditions other than obesity accompanied by adipose tissue inflammation, such as atherosclerotic vascular disease and type 2 diabetes and that these levels are associated with disease severity 17 20 39 40 41 . Because, some of these conditions are risk factors for HF development, further studies are needed to investigate whether circulating ANGPTL2 affects cardiac function.…”
Section: Discussionmentioning
confidence: 89%
“…21,29-35, 56 We found that serum ANGPTL2 levels are associated with obesity, as estimated by body mass index and abdominal circumference, in the general Japanese population. 17 Moreover, in overweight Japanese subjects, decreased serum ANGPTL2 levels reflect positive effects of lifestyle intervention in terms of weight loss and improved metabolic parameters, such as triglyceride (TG) and/or insulin activity and the homeostasis model assessment-insulin resistance (HOMA-IR) index.…”
Section: Circulating Angptl2 Levels In Cvd and Predisposing Conditionsmentioning
confidence: 80%
“…59 A 10-year follow-up in an epidemiological study of the general Japanese population with no history of CVD revealed that elevated serum ANGPTL2 levels correlated with future de novo development of CVD, independent of risk factors such as high hs-CRP levels. 56 Moreover, in a prospective, monocentric cohort of European patients with type 2 diabetes but without end-stage renal disease (followed for a median of 6.0 years with death as a primary endpoint and major adverse CV events (known as MACE) such as death, myocardial infarction or stroke as a secondary endpoints), serum ANGPTL2 concentrations were independently associated with death and MACE. 60 Taken together with observations suggesting that ANGPTL2 promotes CVD development and progression in mice, 25 circulating ANGPTL2 levels could be viewed as a candidate biomarker for risk stratification relevant to CVD development and progression in both type 2 diabetic patients and…”
Section: Circulating Angptl2 Levels In Cvd and Predisposing Conditionsmentioning
confidence: 99%
“…In the Hisayama cohort study including 3005 Japanese general population aged ≥40 from 1988, serum levels of angiopoietin-like protein 2-a proinflammatory mediator that promotes endothelial dysfunction-were positively correlated with the risk for future cardiovascular disease. 78 Saita et al 79 showed that plasma levels of soluble endoglin-a transforming growth factor-β receptor highly expressed on proliferating endothelial cells-were inversely associated with the severity of coronary artery disease. Given that conflicting results have been reported earlier in diabetic patients, 80 whether endoglin can serve as a biomarker for coronary artery disease awaits further investigation.…”
Section: Biomarkersmentioning
confidence: 99%